2020
DOI: 10.17269/s41997-020-00451-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary attack rate of COVID-19 in household contacts in the Winnipeg Health Region, Canada

Abstract: Objectives Understanding important transmission parameters, such as secondary attack rates, can help in strategizing, prioritizing, and planning interventions to curb morbidity and mortality due to COVID-19. Early reports suggest the risk of transmission of SARS-CoV-2 (the pathogen that causes COVID-19 disease) is high among household contacts of cases. The purpose of this analysis was to determine the household transmissibility of SARS-CoV-2 in residents of the Winnipeg Health Region. Methods We extracted inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…Moreover, Pujadas and colleagues showed that high viral load was correlated to higher mortality rates, suggesting to use quantitative analyses for patient risk-strati cation [10], thus, high viral load could act a key role in the severity of COVID-19. These ndings were supported by other studies reporting an association between high viral loads and more severe symptoms [6][7][8][9][10][11]17]. Otherwise, other studies did not show any statistically signi cant difference in viral loads between symptomatic and asymptomatic individuals [10][11][12][13][14][15][16][17][18]20], while Hasanoglu and colleagues showed that higher viral loads were found in asymptomatic patients when compared to symptomatic ones and that, the more the clinical course of the diseases was severe, the lower viral loads were observed, together with a signi cant negative trend with increasing age [5].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, Pujadas and colleagues showed that high viral load was correlated to higher mortality rates, suggesting to use quantitative analyses for patient risk-strati cation [10], thus, high viral load could act a key role in the severity of COVID-19. These ndings were supported by other studies reporting an association between high viral loads and more severe symptoms [6][7][8][9][10][11]17]. Otherwise, other studies did not show any statistically signi cant difference in viral loads between symptomatic and asymptomatic individuals [10][11][12][13][14][15][16][17][18]20], while Hasanoglu and colleagues showed that higher viral loads were found in asymptomatic patients when compared to symptomatic ones and that, the more the clinical course of the diseases was severe, the lower viral loads were observed, together with a signi cant negative trend with increasing age [5].…”
Section: Introductionsupporting
confidence: 86%
“…The disease clinical course is characterized by several factors, from asymptomatic to mild or severe viral respiratory tract infections, up to systemic in ammation and thrombosis [5]. Several other risk factors have also been identi ed to affect the disease course, such as gender, concomitant diseases, close contact and age [5,8]. Indeed, Centers for Disease Control and Prevention (CDC) has identi ed 65 years old and older people at a greater risk of hospitalization and death for COVID-19, from 90x higher risk of death for 65-74 years old, up to 630x higher for over 85 years old people [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the SAR for 28 studies 12,14,17,27,94 from January to February 2020 (13.4%; 95% CI, 10.7%-16.7%), the SAR was significantly higher for 30 studies 6,7,15,16,19,22,25,26,28,30,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]93 from March to April 2020 (19.4%; 95% CI, 15.2%-24.5%; P = .03) and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021 (31.1%; 95% CI, 22.6%-41.1%; P < .001) but not significantly different from the SAR for 14 studies…”
Section: Resultsmentioning
confidence: 80%
“…Characteristics of Studies Included in Analysis of Household Secondary Attack Rates for SARS-CoV-2 (continued) ,23,24,29,37,40,45,79,[88][89][90]92 21.0(13.8-30.6) No 75[4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][25][26][27][28][30][31][32][33][34][35][36][37][38][39][74][75][76][77][78][80][81][82][83][84]…”
mentioning
confidence: 99%
“…In the USA, secondary attack rates were estimated between 0.5-53% [15,16,18,19]. In Canada, a 14.7% secondary infection rate was calculated [20]. A meta-analysis estimated the rate to be around 17% [21].…”
Section: Plos Pathogensmentioning
confidence: 99%